Inclusive Product Design: Applicating the Montessori Methodology into the Design Conception of Children’s Products - Moreira, Leonardo [UNESP]; Barata, Tomás Queiroz Ferreira (Springer Nature, 2022)
This article presents the results of an ongoing scientific initiation research, as well as the contributions attained from a Research Internships Abroad Program (BEPE/FAPESP) which sought to expand the theoretical framework on design processes regarding sensory products in the European Market. The study focuses on toys for children with blindness or low vision, including its design process, all the way though its physical prototyping. Here follows the adopted structure of analysis: (a) Theoretical review on the design of sensory products and the contribution of the Montessori method; (b) Application of synchronous analysis amid similar children’s toys from the European market, specifically those commercialized in Portugal; (c) Project development with generation and selection of alternatives; (d) Experimental execution of the physical prototype at the Prototype Laboratory. Thus, this research aims to contribute to the development of sensory products through the Montessori method, as well as stimulating further research in the areas of Product Design and Inclusive Design.
Keywords: Inclusive design; Montessori method; Product design; Sensory products